Relationship-Based Music Intervention for a Child with Developmental Disorder and Visual Impairment - Zishan Xiong (Ilmu Inovasi Nusantara, 2025)
This clinical portrait investigates the implementation of a relationship-based musical intervention (RBMI) for a 9-year-old girl diagnosed with Neurodevelopmental Disorder and Visual Impairment in a school setting. Despite the growing body of research highlighting the effectiveness of music therapy across various populations, its application in the context of special education remains limited. Existing studies indicate that music interventions can positively impact individuals with developmental disorders, fostering improvements in communication, social interaction, and emotional well-being (Cibrian et al., 2020; Imankhah et al., 2018; Jacob & Pillay, 2021; Thompson & McFerran, 2015). However, further clinical exploration is essential to substantiate these claims with robust evidence. The RBMI approach in this study leveraged a therapeutic alliance to enhance the participant’s engagement with music and support her social, communicational, and visual development. A qualitative methodology utilized diverse data collection techniques, including field notes, reflective journals, and artistic responses. These tools facilitated an in-depth understanding of the participant’s progress and the nuanced dynamics of the therapeutic relationship. Findings from the study revealed that the therapeutic relationship catalyzed the participant’s positive engagement with the music-based intervention. The natural progression of this alliance fostered meaningful interactions, which contributed to notable advancements in her social and communicative abilities. Based on these results, the study recommends the integration of RBMI within particular education frameworks to enhance developmental outcomes for children with disabilities. Future research should aim to expand on these findings by incorporating larger participant samples and longitudinal assessments